Integrasi Pendekatan Teoritis dan Implementasi Perencanaan Pendidikan di Indonesia: Analisis Kesenjangan dan Solusi Strategis - M. Ihsan Al Fikri; Fadhilah Fadhilah; Asmendri Asmendri; Milya Sari (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to analyze the fundamental concepts, principles, and implementation challenges of educational planning through a systematic literature review. Employing qualitative methods with a library research design, this study synthesized 25 academic sources, including journals, textbooks, and policy documents published within the last decade. The analysis reveals that educational planning encompasses systematic processes of needs analysis, goal formulation, priority setting, implementation, and evaluation. Three major approaches—social demand, manpower needs, and rate of return—emphasize equity, relevance, and efficiency, respectively. Four critical aspects (quantitative, qualitative, relevance, and efficiency) must be comprehensively integrated throughout the planning stages. The findings indicate substantial implementation challenges, including limited managerial capacity, insufficient data literacy, weak stakeholder participation, and resource constraints. School Work Plans (RKS/M) often remain administrative documents rather than strategic instruments for institutional improvement. Regional disparities in planning capacity further exacerbate educational inequity between urban and rural areas. Significant gaps persist between theoretical concepts and practical implementation, where planning becomes a mechanistic administrative task rather than a strategic management instrument. This study concludes that effective educational planning requires paradigm transformation toward participatory, evidence-based approaches supported by enhanced capacity building, systematic evaluation mechanisms, and synergistic coordination among central government, regional authorities, and educational institutions to ensure sustainable and equitable national education development.